Estetika Pertunjukan Tari Kerincingan di Sanggar Elsando Kota Tegal - Sytha Dwi Afifah Nashrulmillah; Lesa Paranti (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This research examines the aesthetics of the Kerincingan Dance performance at Sanggar Elsando Kelurahan Mintaragen, Kecamatan Tegal Timur, Kota Tegal. Tari Kerincingan is a popular creative dance created in 2014, depicting cheerfulness and agility in its group movement composition. The research problem is how the aesthetics of Tari Kerincingan manifest at Sanggar Elsando Kota Tegal, with the aim of describing and analyzing its performance aesthetics. This study employs a qualitative method with an aesthetic-choreographic approach. Data collection techniques include direct observation of the studio's condition, rehearsal processes, and dance performances, structured and unstructured interviews with the dance creator, as well as documentation in the form of images, video, and sound recordings. Data validity was tested through triangulation of sources, methods, and theories. Data were analyzed systematically through data reduction based on the classification of main and supporting dance elements, dance movement techniques, and dance aesthetics; data presentation with descriptive information on dance aesthetics complemented by photographs; and conclusion drawing. The results indicate that the aesthetics of Tari Kerincingan are evident in its form, which includes cheerful, agile, energetic, and dynamic movements. Its content portrays the cheerfulness and agility of teenage girls as entertainment, with a message of spirit reinforced by the sound of kerincingan. Its presentation includes corrective makeup, gold-themed costumes, Javanese gamelan accompaniment and the kerincingan itself, along with other suitable performance elements. This aesthetic quality is further enhanced by the harmony among these three aspects, creating unity, dominance, and balance.